(untitled) (Research, Society and Development, 2024)
The objective of this work was to evaluate the availability of phosphorus for corn over 8 weeks in the 10-20 cm layer of soil. The experiment was conducted on a rural property in Paraguaçu/MG, where the soil was prepared and corn (Híbrido Brevant B2401PWU) was sown on 03/02/2024, with the application of three different sources of phosphorus: Fosbio®BR24, Fosfato natural, and Mono Ammonium Phosphate (MAP), in addition to two controls (with and without corn). The experimental design was in randomized blocks with four replications and a 3x2 factorial arrangement. Soil analyzes occurred weekly, with 10 subsamples per plot. The presence of corn had a variable impact on P availability, depending on the source used. Fosfato natural was more affected by the presence of corn, while Fosbio®BR and MAP maintained more constant P levels. Fosbio®BR and MAP were effective in maintaining P availability, regardless of the presence of corn, indicating that they are reliable sources of P for the soil. On the other hand, Fosfato natural was more sensitive to soil conditions and the presence of corn. Fluctuations in P availability suggest that the dynamics of phosphorus release are influenced by several factors, such as the type of fertilizer, the presence of crops and possibly other environmental conditions, and it is important to consider the interaction between the phosphorus source and the crop at hand. plan soil fertilization, as the appropriate choice of fertilizer can significantly influence the availability of essential nutrients, such as phosphorus, over time.